Prior Bexarotene or Phototherapy Does Not Affect Response to Chlormethine Gel: Post Hoc Analysis of a Pivotal Trial - Chalid Assaf; Christiane Querfeld; Marta Scandurra; Marco Turini; Julia J. Scarisbrick (Medical Journals Sweden, 2023)
Abstract is missing (Short communication)